1990
DOI: 10.1002/cber.19901231012
|View full text |Cite
|
Sign up to set email alerts
|

Neue Dienophile und Diene, III. Über die Addition von Cyanacetylen an [2.2]Paracyclophan

Abstract: New Dienophiles and Dienes. 111'). -On the Addition of Cyanoacetylene to [2.2 ]ParacyclophaneHeating a benzene solution of [2.2]paracyclophane (2) in the presence of excess cyanoacetylene (lb) at 160°C in a sealed ampoule provides the novel 2: 1-addition product 10, as well as the previously obtained cycloadducts 7-9. It is suggested that these Nenitzescu hydrocarbon systems are formed via the cyclobutadiene intermediates l? and 18. This hypothesis is supported by the isolation of the side-products 1,2,4-and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1990
1990
2010
2010

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Compound (II) was prepared from cyanoacetylene, (I), as previously described (Witulski et al, 1990); the spectroscopic and analytical data were consistent with those reported previously. Single crystals were obtained by slow cooling from carbon tetrachloride.…”
Section: Methodsmentioning
confidence: 69%
See 1 more Smart Citation
“…Compound (II) was prepared from cyanoacetylene, (I), as previously described (Witulski et al, 1990); the spectroscopic and analytical data were consistent with those reported previously. Single crystals were obtained by slow cooling from carbon tetrachloride.…”
Section: Methodsmentioning
confidence: 69%
“…Heating cyanoacetylene, (I), at 433 K results in the formation of 1,2,4-and 1,2,3-tricyanobenzene, (II); we have shown that this trimerization involves the intermediate generation of tricyano-Dewar benzenes (Witulski et al, 1990). We now report the crystal structure of (II).…”
Section: Commentmentioning
confidence: 80%
“…Synthesis of 1,2,3‐ and 1,2,4‐tricyanobenzene (13 and 14) : Although both compounds could be prepared by trimerization of cyanoacetylene ( 1 , see above), this route is rather involved and requires extensive separation work 8a,b. e Fortunately, both isomers have been prepared previously by the simple routes summarized in Scheme , both of them having been reported in the literature 11…”
Section: Resultsmentioning
confidence: 99%
“…Preparative methods : The tricyanobenzenes 13 and 14 were prepared by the routes described in reference 11 and characterized by the usual spectroscopic and analytical methods as summarized in reference 8a, b.…”
Section: Methodsmentioning
confidence: 99%